Rheological Study on Strength Characteristics of Sandcrete Hollow Block Admixed with Oil Palm Stem Ash - A. T., Adeyokunnu; F.O., Adeyemi; L.A., Afolabi (Engineering And Technology Journal, 2022)
The study investigated the use of oil palm stem ash as partial replacement of OPC for sandcrete hollow block production which ranges from 0 to 25% (at 5% interval). Ninety six (96) sandcrete blocks were cast using 1:6 as mix ratio of cement: sand with 0.45 water cement ratio. The compressive strength, density, porosity and abrasion test were carried-out on sandcrete block were tested at curing age 7, 14, 21 and 28 days. The oil palm stem ash was analysed for chemical composition of (SiO2, Al2O3 and Fe2O3) in which the summation is 75.3%. it was observed that compressive strength and bulk density decreases as the content of OPSA increases but 5% of OPSA has value of 4.66N/mm2 and 2111.20Kg/m3 as against the control 5.12N/mm2 and 2162.01Kg/m3 respectively. The porosity and abrasion test revealed the increase in value as the percentage content of OPSA increased. It was concluded that OPSA is a good pozzolan having satisfied the required standard. which can be used as 10% of OPSA content insandcrete hollow block production having attained a 28 day compressive strength of more than 3.5N/mm2 as required by the Nigeria National Building Code (2007) for non load bearing wall.